Selected Profile of Psychiatric Patients Admitted in a Specialized Hospital (KYAMC Journal, 2017)
The current study had been carried out on the admitted patients in Mental Hospital, Pabna who was admitted during the calendar year 2008. Mental patients having only psychotic type (major) of illness are admitted in this hospital. A total of 101 (one hundred and one) admitted patients were included in the study. Among them, male patients were 79 (78.22%) and females were 22 (21.78%). Their age ranges from 19 (nineteen) to 48 (forty eight). The mean age of the patients was 27.35. Among the respondents, 21 to 30 year age group population found suffering more (46.54%) in this study than other age group. The number of the first group people is a few which may be due to the small age span. More than half (55.45%) of the cases were unmarried. Secondary and Higher secondary educated people occupies more than half (57.43%) of the respondents. Illiterate group population occupies the third (12.87%) position. More than half ( 55.45%) of the cases do not have any job during the time of admission. About two-thirds (63.37%) of the cases were from rural background and more than half (58.42%) were diagnosed as Schizophrenics. Schizo- affective disorder (25.74%) occupies the second position so far the diagnosis of the respondents were concerned. Most of them (81.19%) did not give any positive family history of mental illness. More than two-thirds (66.34%) of the cases have given the history of taking mixed type of treatment before attending the OPD of Mental hospital, Pabna.KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 770-774